2005
DOI: 10.1007/s10750-005-4302-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Pesticides on Reproduction of Rotifer Brachionus plicatilis Müller

Abstract: Pesticides have been major contributors to environmental pollution and they are now widely distributed in aquatic environments. Zooplankters are frequently used as test animals to detect aquatic contaminants because of their sensitivity and ecological importance. We investigated the effect of a 7-day exposure to four commonly used pesticides (diazinon, fenitrothion, methoprene and isoprothiolane) on reproduction of the rotifer Brachionus plicatilis. Pesticide concentrations of 3-7 times lower than the 24-h 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 26 publications
9
30
1
3
Order By: Relevance
“…Regardless of the mechanisms driving this trend, our results suggest that significant toxicological effects may be observed in parameters related to the production and quality of diapausing eggs, although gross endpoints, such as population growth rate, are insensitive to toxicants. In rotifers there is broad evidence that the sexual phase can be more sensitive to environmental conditions, specifically exposure to toxicants, than the asexual phase (Snell and Carmona 1995;Snell et al 1999;Preston and Snell 2001;Marcial et al 2005). Our results are in agreement with those antecedents, but in addition this study provides interesting information about the adaptive value of the diapause strategy against adverse conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Regardless of the mechanisms driving this trend, our results suggest that significant toxicological effects may be observed in parameters related to the production and quality of diapausing eggs, although gross endpoints, such as population growth rate, are insensitive to toxicants. In rotifers there is broad evidence that the sexual phase can be more sensitive to environmental conditions, specifically exposure to toxicants, than the asexual phase (Snell and Carmona 1995;Snell et al 1999;Preston and Snell 2001;Marcial et al 2005). Our results are in agreement with those antecedents, but in addition this study provides interesting information about the adaptive value of the diapause strategy against adverse conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, because only the asexual portion of the life cycle is commonly investigated in toxicity studies, the true vulnerability of zooplankton to toxicants is often underestimated (Preston and Snell 2001;Navis et al 2015). Several studies assessed the effects of pesticides, heavy metals, and endocrine-disrupting chemicals on sexual reproductive parameters of rotifers (Snell and Carmona 1995;Preston et al 2000;Yoshinaga et al 2000;Preston and Snell 2001;Radix et al 2002;Marcial et al 2005;Ríos-Arana et al 2007) and cladocerans (Tatarazako and Oda 2007;Navis et al 2013Navis et al , 2015. Their results showed that, depending on the species and contaminants tested, reproductive parameters such as mixis ratio (i.e., proportion of sexual females relative to all females, sexual and asexual) and fertilization, and diapause parameters such as resting egg production and resting egg hatchability are among the most sensitive endpoints to assess toxicity in zooplankton species.…”
Section: Introductionmentioning
confidence: 99%
“…The general hypothesis that repression of sexual reproduction was a general response to environmental stresses of many types (Lubzens et al, 1985;Snell, 1986;Snell and Boyer, 1988;Snell and Carmona, 1995;Preston et al, 2000;Xi and Feng, 2004;Marcial et al, 2005;Xi et al, 2007). Similar results were obtained in the present study for dieldrin, chlordecone and b-HCH.…”
Section: Resultssupporting
confidence: 91%
“…In the present study, dieldrin and b-HCH at higher concentrations decreased significantly the FR, which was similar to the result of DDT , but aldrin and chlordecone had no significant effect on it, which was similar to the results of pentachlorophenol, cadmium and naphthol (Snell and Carmona, 1995), dicofol, lindane and endosulfan , chlorpyrifos, flutamide, testosterone, nonylphenol, diazinon, fenitrothion, methoprene and isoprothiolane (Preston et al, 2000;Marcial et al, 2005), and cypermethrin and deltamethrin (Huang et al, 2011). It is possible that lower production of males is one of the reasons which decreased the FR of rotifers.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation